Achieving Highly Efficient Nonfullerene Organic Solar Cells with Improved Intermolecular Interaction and Open‐Circuit Voltage. Issue 21 (29th March 2017) - Yao, Huifeng; Ye, Long; Hou, Junxian; Jang, Bomee; Han, Guangchao; Cui, Yong; Su, Gregory M.; Wang, Cheng; Gao, Bowei; Yu, Runnan; Zhang, Hao; Yi, Yuanping; et al.
Abstract : A new acceptor–donor–acceptor‐structured nonfullerene acceptor ITCC (3, 9‐bis(4‐(1, 1‐dicyanomethylene)‐3‐methylene‐2‐oxo‐cyclopenta[ b ]thiophen)‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐ d ′:2, 3‐ d′ ]‐s‐indaceno[1, 2‐ b :5, 6‐ b′ ]‐dithiophene) is designed and synthesized via simple end‐group modification. ITCC shows improved electron‐transport properties and a high‐lying lowest unoccupied molecular orbital level. A power conversion efficiency of 11.4% with an impressive V OC of over 1 V is recorded in photovoltaic devices, suggesting that ITCC has great potential for applications in tandem organic solar cells. Abstract : A new acceptor–donor–acceptor‐structured nonfullerene acceptor, ITCC, is designed and synthesized via simple end‐group modification. ITCC shows improved electron‐transport properties and a high‐lying lowest unoccupied molecular orbital level. A power conversion efficiency of 11.4% with an impressive V OC of over 1 V is recorded in photovoltaic devices, suggesting great potential for applications in tandem organic solar cells.